Bibliometric Insights of Global Research Landscape in Mitophagy - Li, Guoli; Yin, Wei; Yang, Yiya; Yang, Hongyu; Chen, Yinyin; Liang, Yumei; Zhang, Weiru; Xie, Tingting (Frontiers in Molecular Biosciences, 2022)
Background: Autophagy is a highly regulated and evolutionarily conserved process in eukaryotes responsible for protein and organelle degradation. Although this process was described over 60 years ago, the selective autophagy of mitochondria (mitophagy) was recently coined in 2005. Research on the topic of mitophagy has been rapid progress in the past decade, which proposed to play critical roles in human health and disease. The aim of this study was to visualize the scientific outputs and research trends of mitophagy. Methods: Articles and reviews related to the topic of mitophagy were retrieved from the Web of Science Core Collection on November 30, 2021. Two kinds of software (CiteSpace and VOSviewer) were used to perform visualized analysis of countries/regions, institutions, authors, journals, references and keywords. Results: From 2005 to 2021, 5844 publications on mitophagy were identified for final analysis. The annual number of publications growing exponentially over the past 17 years. USA (N=2025) and Chinese Acad Sci is the leading country and institute (N=112) ranked by the number of publications, respectively. The most productive author was Jun Ren (N= 38), and Derek P Narendra obtained the most co-cited times (2693 times). The journals with the highest output and the highest co-citation frequency were Autophagy (N=208) and Journal of Biological Chemistry (co-citation: 17226), respectively. Analysis of references and keywords suggested that “mechanism of mitochondrial quality control”, “molecule and signaling pathway in mitophagy” and “mitophagy related diseases” were research hotspots, and parkin-mediated mitophagy and its roles in skeletal muscle and inflammation related diseases may be the frontiers of future research. Conclusion: Although mitophagy research has flourished and attracted attention from all over the world, the regional imbalance of development of mitophagy research was observed. Our results provided a comprehensive global research landscape of mitophagy from 2005 to 2021 in a perspective from bibliometrics, which may serve as a reference for future mitophagy studies.